The Influence Of The Discovery Learning Model for the Result of IPS Subject Grade V UPTD SD 124385 Pematang Siantar - Siti Agustina Manik; Muktar B Panjaitan; Rio Parsaoran Napitupulu (MultiTech Publisher, 2023)
The background to this research is based on observations made by researchers in class V UPTD SD Negeri 124385 Pematang Siantar, where teachers still use conventional learning models, resulting in low student learning outcomes. From the problems that exist in the class, it is necessary to find a solution, namely by applying the Discovery Learning learning model. This learning model is suitable for use in all subjects and this model is suitable for use in class V because this learning model invites students to find their own conclusions from learning. This research used a pre-experimental method with a One Group Pretest-Posttest design with a sample of 25 students. Based on the results of the power analysis test used, the Hypothesis Test results obtained were T = 15.469 and T table = 2.064 with T count > T table = 15.469 > 2.064, so Ho was rejected and Ha was accepted. With this explanation, it can be concluded that there is an influence of the Discovery Learning learning model on student learning outcomes in class V UPTD SD Negeri 124385 Pematang Siantar.